BIOHERBISIDA SEBAGAI PENGARUH NEGATIF TERHADAP TANAMAN BAWANG DAUN - cahyati, novia; Sutanto, Agus (Universitas Muhammadiyah Metro, 2021)
Indonesia is a tropical country that has a high biodiversity of both its flora and fauna.Plants are able to flourish both with high economical value as well as plants that have no high economical value.Growth that does not have a high economical value one of them is weed crops.Weed crops flourish in agricultural and plantation areas. The presence of this weed plant is able to mangakibatkan the underlying plant is disturbed growth because weed plants have the same condition of growing with the staple plants then need to be held weed crop control to improve the production of staple crops.Weeds and Babadotans have active compounds that can inhibit the growth of staple crops.The mechanism of action of alelopathy is able to inhibit crops in absorbing nutrients from the environment and affect the normal growth of plants.The roots are entrances for nutrients and water from the ground, which is essential for the soil's physiological process.Water absorption barriers caused the process of photosynthesis because water is a raw material of photosynthesis.In addition the process of exchanging water, CO2, and O2 in the stomata of the leaves needed in the metabolism of corn seedlings is hindered due to the impact of the alelopathy of weed extracts, resulting in a decrease in wet weights and stunted photosynthesis caused a slightly low dry weight.The mechanism of alelopathy is able to reduce the content of chlorophyll and the rate of photosynthesis.